GOVERNMENT REVENUE-EXPENDITURE NEXUS: EVIDENCE FROM SEVERAL TRANSITIONAL ECONOMIES - Konukcu-Önal, Debi; Nil Tosun, Ayse (Economic Annals, 2008)
Budget deficits and the debate on the sources of deficit finance have been on the agenda of public economics ever since the 1980s. However recently in the post-communist countries fiscal imbalances appear to be an important problem due to prolonged periods of growing poverty resulting from the transition process. Poverty alleviation policies considerably affect the revenue and expenditure decisions of governments, which are subject to hard budget constraints in an open transitional economy and do not have room for departing from sound fiscal policies. The public finance literature provides a vast number of studies analyzing the relationship between public revenues and expenditures. These studies are mostly characterized by efforts to reveal the attitude of the fiscal authority towards maintaining the budget balance. In this respect, budgetary dynamics in which past government revenues have predictive power on the current level of government expenditures are accepted as evidence of the so-called tax-and-spend hypothesis. On the other hand, the revenue-expenditure nexus running from expenditures to revenues is known in the literature as the spend-and-tax hypothesis. The objective of this study is to analyze empirically the relationship between government revenues and expenditures in four of the transitional economies, i.e. Belarus , Kazakhstan , the Kyrgyz Republic and the Russian Federation . The empirical findings of this study, which are based on Granger causality tests, indicate evidence supporting the tax-and-spend hypothesis in Belarus and the Russian Federation and fiscal synchronization in Kazakhstan and the Kyrgyz Republic . The empirical support for the tax-and-spend hypothesis in these economies implies that increasing government revenues may not end up with lower budget deficits due to their stimulating effect on the demand for public goods and services.